Alternative learning approaches for electronic learning environments in smart schools: survey results - Krishnasamy, Kemalatha; Lee, Sai Peck; Palaniappan, Ananda Kumar (2006)
Learning styles have been studied for many years; however, studies focusing on learning styles based on multiple intelligences theory for electronic learning are very limited. Knowledge of learning styles is important and may be useful in the development and conduct of e-learning in higher learning institutions and schools. The purpose of this study was to establish baseline information regarding the distribution of learning styles among lower secondary students at selected smart schools in Malaysia. A secondary purpose was to establish for these same individuals their stated preferred learning mode for learning online. A purposive sample (judgment sampling) was developed with permission from Ministry of Education and Education Departments in Malaysia. The learning style for each respondent was determined using the multiple intelligences inventory. The results of the study showed that, web-based instruction in its present form was more preferred by students whose intelligences were visual/spatial and interpersonal. Verbal/linguistic and logical/mathematical students reported less benefit from e-learning, perhaps because these students were more oriented towards traditional classroom learning. Keywords: E-learning, online teaching and learning, multiple intelligences, effective design.